Linear maltodextrin polymer–folic acid modified graphene oxide nanoparticles for targeted delivery and pH/photothermal sensitive release of hydrophobic anticancer drugs in tumor cells. (13th December 2022) - Li, Xiaoning; Zhu, Huirui; Xing, Zihan; Gong, Tao; Li, Meining; Su, Dan; Liang, Wenting; Guo, Rui
Abstract : GO@LM-SP-FA was constructed by connecting linear maltodextrin polymer and folic acid to the surface of graphene oxide nanoparticles. Doxorubicin hydrochloride was loaded into GO@LM-SP-FA to form GO@LM-SP-FA/DOX, and controlled release of anticancer drugs was realized. Abstract : A novel multifunctional graphene oxide nano drug carrier (GO@LM-SP-FA) was constructed by connecting a linear maltodextrin polymer (LM-SP) and folic acid (FA) to the surface of graphene oxide (GO) nanoparticles. Doxorubicin hydrochloride (DOX) as a model drug was loaded onto the GO@LM-SP-FA through π–π stacking, hydrogen bonding and hydrophobic interaction. The GO@LM-SP-FA nanomaterial possessed excellent photothermal conversion efficiency, double-targeted drug delivery and near-infrared light (NIR)/pH triggered drug release. More importantly, GO@LM-SP-FA combined the cancer cell targeting of FA, showing excellent cancer-killing efficiency in HeLa (78%) and MCF-7 (61%). Therefore, the novel nano-drug carrier synthesized in this paper has potential practical application value in the treatment of cancer, especially in cervical cancer which has high FA expression.